The Psychometric Properties of the Norwegian version of The Crowell procedure - Stormark, Kjell Morten; Vis, Svein Arild (PsykTestBarn, 2022)
Description: The Crowell procedure is developed to test child-parent interaction during a sequence of nine different tasks that takes about 45 minutes to complete. It was developed by Crowell and colleagues at Stanford University, USA in 1988 and has since then been revised several times. An unpublished Norwegian version is available. Parental-child interaction is scored on scales related to the two main dimension which are (i) child behaviors and (ii) parental support and behavior during task completion. The child dimension is divided into seven subscales and the parent dimension has five subscales. There are no known formal requirements for competence for the use of the procedure. Training is provided in the form of a three-day course. Literature search: No relevant Scandinavian publications were identified. Psychometrics: The literature search resulted in no documentation on the psychometric properties of the Norwegian version of the Crowell procedure. Conclusion: Measurement properties of the Norwegian version is unknown.